GAMBARAN PENGELOLAAN HAMBATAN MOBILITAS FISIK PADA PASIEN STROKE NON HEMORAGIK DENGAN LATIHAN GENGGAM BOLA - Sri Hesthi Sonyorini; Sulastri Sulastri (Jurnal Surya Muda, 2023)
Introduction: Stroke is a neurological disease that occurs suddenly causing blockages in cerebral blood vessels, both total and partial blockages that occur over a period of 24 hours. Stroke is damage to the brain that appears suddenly, progressively and rapidly due to non-traumatic cerebral blood circulation disorders. The disorder suddenly causes symptoms, including paralysis of the face or limbs, speech is not fluent, speech is not clear (pelo), changes in consciousness, visual disturbances, etc. Objectives to identify the description of the management of Physical Mobility Barriers in Non-Hemorrhagic Stroke Patients with Exercise Hold the Ball. Methods: This type of research is quantitative, descriptive research, the sample is 32 respondents, using total sampling. The measuring instrument used in this research is a questionnaire sheet and an observation sheet, data analysis using univariate. Results: The results showed that the majority of respondents who managed physical mobility barriers in non-hemorrhagic stroke patients with good ball grip exercise were 19 (59.4%). Suggestion: It is hoped that the results of this study can be used as information material for the public to use handheld ball exercises in non-hemorrhagic stroke patients